Kepuasan Mahasiswa Terhadap Bimbingan dan Konseling Akademik Secara Daring oleh Dosen Pembimbing Akademik - Eliza, Fivia; Mudjiran; Neviyarni; Nirwana, Herman; Sardi, Juli; Habibullah (Information Technology Education Department, 2024)
In the growing digital era, online academic guidance and counseling is a practical solution in supporting students in achieving student academic success. This article aims to explore the level of student satisfaction with academic guidance and counseling provided online by academic supervisors in the Electrical Engineering Study Program at Padang State University. The research method in this study uses a quantitative approach with a questionnaire instrument. Data were analyzed with descriptive statistics. The results of this study indicate a fairly high level of satisfaction from students towards academic guidance and counseling conducted by academic supervisors online. The findings of this study provide valuable insights for universities in understanding the needs of students related to guidance and counseling in the digital era. This research opens up future research opportunities to develop a more interactive and user-friendly platform to support online academic guidance and counseling.